Happiness and surprise are associated with worse truth discernment of COVID-19 headlines among social media users in Nigeria - Leah R. Rosenzweig (Harvard Kennedy School, 2021)
Do emotions we experience after reading headlines help us discern true from false information or cloud our judgement? Understanding whether emotions are associated with distinguishing truth from fiction and sharing information has implications for interventions designed to curb the spread of misinformation. Among 1,341 Facebook users in Nigeria, we find that emotions—specifically, happiness and surprise—are associated with greater belief in and sharing of false, relative to true, COVID-19 headlines. Respondents who are older, are more reflective, and do not support the ruling party are better at discerning true from false COVID-19 information.